2017
DOI: 10.1097/jom.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

The Employer Perspective on Sustainable Employability in the Construction Industry

Abstract: Implementation of measures aimed at reducing physical load and the promotion of personal development are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…First, although physical capacity declines as a natural process of aging (Hamberg-van Reenen et al 2009; Soer et al 2012), some studies among older employees in physically demanding occupations have found that capacity is maintained with age (Gall and Parkhouse 2004; Schibye et al 2001; Torgen et al 1999). Second, the recommendation of lowering occupational physical demands with age is not always followed (Aittomaki et al 2005; Burr et al 2017; Jarvholm et al 2014; Jebens et al 2014; Tonnon et al 2017). Third, both decreases and increases in relative physical strain with age have been reported (Brighenti-Zogg et al 2016; Gupta et al 2014; Jebens et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…First, although physical capacity declines as a natural process of aging (Hamberg-van Reenen et al 2009; Soer et al 2012), some studies among older employees in physically demanding occupations have found that capacity is maintained with age (Gall and Parkhouse 2004; Schibye et al 2001; Torgen et al 1999). Second, the recommendation of lowering occupational physical demands with age is not always followed (Aittomaki et al 2005; Burr et al 2017; Jarvholm et al 2014; Jebens et al 2014; Tonnon et al 2017). Third, both decreases and increases in relative physical strain with age have been reported (Brighenti-Zogg et al 2016; Gupta et al 2014; Jebens et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These perceptions echo those of Dutch blue collar construction workers surveyed about sustainable employability, who ranked highly the need to reduce physical job demands [34]. Although this was also frequently mentioned by a parallel survey of Dutch construction employers, only one in five had actually listed reducing physical workloads as being “on the company agenda”, citing cost, time and client demands as barriers [33]. Interventions aimed at planning, administrative controls and engineering assistive devices, along with improved approaches to temporary as well as permanent workplace accommodations, are widely seen to benefit workers entering the trades, as well as those attempting to continue to work at older ages.…”
Section: Discussionmentioning
confidence: 73%
“…As previously found among blue collar construction workers and construction employers [33,34], participants identified opportunities for career pathways to enable construction workers to reduce physical demands. Both individual unions and NABTU offer an array of continuing education and training programs to foster the acquisition of management, training, or safety skills.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…: worker is not open to change and little willingness of the worker if there is no work disability. The participation of workers also seems important in improving sustainable employability, since a passive attitude was considered as a barrier for sustainable employability in the construction industry [30]. Another important factor for implementing preventive measures for the employer is the acquisition of more knowledge about the risk factors, since the employer plays an important role in generating these risk factors [29].…”
Section: Discussionmentioning
confidence: 99%